Variabilidade pedogênica e valores de referência de qualidade de elementos-traço - Linck, Mara Regina (2018)
Trace elements occur naturally in soils and their contents depend on soil formation factors and pedogenetic processes. The determination of these elements in soils is important for environmental studies such as those that establish the quality reference values (QRV). The objective of this study was to determine how the pedologic variability affects the QRV of trace elements of soils of the Planalto Region, in state of Rio Grande do Sul, Brazil. The physical (texture), chemical and mineralogical attributes of samples from the A -horizon and from the subsurface diagnostic horizons of Latosoils (Bw) and Nitosoils (Bt) were analyzed. According to the multivariate analysis, two groups of soils with similar pedologic development were identified, but it depends on the type of horizon. The QRV of the soils indicated two other groups, which are associated to the soil attributes. The QRV of As, Sb, Se, Ag, Cd, Mo, Pb, Cr, Cu and Zn do not differ between the surface and the subsurface horizons, but the QRV of Ba, Co, Ni and V differ between these horizons. The QRV of these elements differ across some of the studied soils. There are two distinct soils groups of QRV, which can be indentified by using some soil indexes, as the clay or sand content, or the total concentration of Si (SiO2), Fe (Fe2O3) and Mg (MgO), besides the exchangeable Na. However, these groups are not relate to the parent material or to the intemperism indexes, usually employed in soil science studies